SEASONAL OF THERMAL, AERIAL AND ACOUSTIC ENVIRONMENT IN SWINE NURSERY AND FINISHING HOUSING. - BARACHO, MARTHA O.; TOLON, Y. B.; NÄÄS, I. A.; ROJAS, M. (Revista Brasileira de Engenharia de Biossistemas, 2008)
Swine rearing is dependent of the regional and local climate, while the variation due to the yearseasons interferes in the thermal stress suffered by the animals. This research aimed to evaluatethe influence of the time of the day as well as the seasons of the year in the inside environment ofswine nursery and finishing housing under subtropical conditions. The experiment was conductedin a commercial swine farm, and data on dry bulb temperature (DBT), air relative humidity (RH),black globe thermometer (BGT), ammonia concentration and level of noise were recorded in theroom geometrical center at a height of 1.5 m above the floor in six distinct times. Results showedthat the environmental variables (DBT and BGT) were influenced by the season of the year and bythe time of the day. Ammonia concentrations obtained varied along the day, presenting the highestvalues during the afternoon. Noise levels in the nursery were not related to the season of the year;however, the time of the day influenced the noise level.